Land law - Dixon, Martin, (Martin J.); Griffiths, Gerwyn; Lees, Emma (Abingdon, Oxon [UK] : Routledge, 2013)
'You've planned your revision and you know your subject inside out! But how do you apply what you have learned to get the best marks in the examination room? Routledge Q&As give you the ideal opportunity to practice and refine your exam technique, helping you to apply your knowledge most effectively in an exam situation. Each book contains approximately fifty essay and problem-based questions on topics commonly found on exam papers, complete with answer plans and fully worked model answers. Our authors have also highlighted common mistakes as well as offering you tips to achieve the very best marks. What's more, Routledge Q&As are written by lecturers who are also examiners, giving you an exclusive insight into exactly what examiners are looking for in an answer. New editions for 2011-2012 include: An introduction, with essay-writing and exam preparation advice, written specifically to address the unique demands of the subject under consideration.'Extra marks' text boxes offering tips and advice to help those students aiming for top marks to go the extra mile.'Common Pitfalls' text boxes showing where students often trip up or highlighting areas of potential confusion, to help students avoid making some of these common mistakes. Key cases and legislation, highlighted within the text for ease of reference. Boxed answer plans after each question, outlining the major points students should be aiming to convey in their answer. Books in the series are also supported by a companion website offering online essay-writing tutorials, podcasts, bonus Q&As and multiple-choice questions to help you focus your revision more effectively'--
'Routledge Q&As give you the tools to practice and refine your exam technique, helping you to apply your knowledge to maximum effect in an exam situation. Each book contains up to fifty essay and problem-based questions on commonly examined topics, complete with answer plans and fully worked model answers. Our authors have also highlighted common mistakes as well as offering you tips on how to achieve the very best marks. Routledge Q&As are written by lecturers who are also examiners, and the books provide'notes from the examiner' for each question to give you an exclusive insight into exactly what your marker will be looking for in an answer'--
Registered land -- Unregistered land -- Co-ownership -- Successive interests in land -- Leases -- Licences and proprietary estoppel -- Easements -- Freehold covenants -- The law of mortgages -- Miscellaneous problems.
Includes index.
Keywords: Land tenure -- Law and legislation -- England -- Examinations, questions, etc; Land titles -- Registration and transfer -- England -- Examinations, questions, etc; Licenses -- England -- Examinations, questions, etc